Powder coating composition
By using acid-functional polyester resin and glycidyl-functional acrylic resin, the problem of uneven coverage of powder coating on the edges and corners of metal substrates is solved, and efficient and uniform coating formation after single-layer application is achieved, with excellent physical properties and anti-corrosion effects.
Patent Information
- Application Number
- CN202380052793.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-13
- Filing Date
- 2023-07-10
- Publication Date
- 2025-02-28
AI Technical Summary
Existing powder coatings are difficult to achieve uniform coverage at the edges and corners of metal substrates, resulting in poor corrosion resistance and inefficient and inconsistent traditional multi-layer coating methods.
A powder coating composition containing acid-functional polyester resin A, glycidyl-functional acrylic resin B, curing catalyst C and optionally beta-hydroxyalkyl amide D is applied by a single layer and heat cured to form a coating with good edge coverage and corner coverage.
After a single application and thermal curing, coatings with excellent physical properties are achieved, including good smoothness, flexibility, chemical resistance and corrosion resistance, especially with significant coverage at edges and corners.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a powder coating composition, a method of using the powder coating composition to provide a coated substrate with improved edge coverage, a method of preparing a powder coating composition, and an article coated with the powder coating composition.
[0002] Powder coating is an advanced, rapidly developing technology that is widely recognized for its durability, gloss retention, weather resistance, ability to apply high thickness coatings up to 200um, and an unlimited range of colors, finishes, glosses and textures. All of this, plus its ability to prevent corrosion of metal substrates (considering the direct cost of corrosion is very high) makes powder an important technology in the coatings field.
[0003] Additionally, powder coating offers a solvent-free finish and a nearly 100% recyclable process for the uncoated powder coating, making it an important component of sustainable or green building projects that employ low VOC emitting products.
[0004] Even though powder coatings are primarily applied to metal substrates, certain areas, such as corners and edges, are difficult to coat evenly with standard coating applications.
[0005] Low coating thickness on the edges may result in poor corrosion protection, which remains a common problem with current technology.
[0006] Different solutions have been proposed, including for example applying multiple powder coats, where the first coat has low flow, thus providing good edge coverage with a strong orange peel effect, followed by a second coat with better flow, but limited thickness and coverage on the edges. This requires at least two applications, resulting in reduced productivity and increased risk of inconsistencies.
[0007] There remains a need to find a single coating that combines excellent edge coverage and corrosion protection with good flow and general application properties. Background Art
[0008] Corrosion resistance of coatings for agricultural construction equipment is a very important property and for many years powder coating compositions having improved edge coverage have been proposed as a solution to this problem.
[0009] For example, US10940505B2 describes a powder coating with improved edge coverage, which is obtained by applying two layers of powder coating in a dry-to-dry manner, the first layer having a short flat flow and a strong orange peel effect with good edge coverage, and the second layer having a longer flat flow but poor edge coverage, and then curing the two layers together.
[0010] WO 2021 / 174086 A1 describes a powder coating with improved edge coverage, which is obtained by applying a primer layer comprising a catalyst or active ingredient or a rheology modifier for the powder coating and then applying a topcoat.
[0011] Applying two layers makes coating lines less productive, causes process inefficiencies and delays, and adds complexity to end-user activities.
[0012] Meanwhile, combinations of solid superdurable carboxylated polyesters with glycidyl methacrylate (GMA) acrylic resins, optionally in the presence of additional hardeners such as β-hydroxyalkylamides, are known, such as described in JP6567783, in which it is reported that combinations of GMA-based acrylic resins having a specific weight average molecular weight and solubility parameter with carboxylic acid group-containing carboxylated polyesters having a specific solubility parameter and solubility parameter difference provide coatings exhibiting good general properties, including scratch resistance. However, these polyesters contain a large number of OH functional groups (high OH values) that do not participate in the reaction with the GMA-based acrylic resin and β-hydroxyalkylamide, which may result in reduced chemical resistance due to the limited increase in molecular weight of the coating obtained during the curing process.
[0013] Another example is EP0522648A1, which discloses that a combination of a GMA-based acrylic resin and a carboxylated polyester containing at least 15 mol% of 1,4-cyclohexanedicarboxylic acid (CHDA) in a polyacid mixture provides good solvent resistance and impact resistance. However, the polyester described in its examples has a low Tg of 39-44°C due to the presence of a large amount of CHDA. This results in reduced storage stability of the polyester and also reduces the storage stability of the powder coating prepared therefrom. In addition, a high content of CHDA reduces the outdoor durability of the coating compared to a coating prepared from a similar polyester containing a lower content of CHDA. SUMMARY OF THE INVENTION
[0015] It is therefore an object of the present invention to provide a powder coating composition that overcomes the above disadvantages. Another object of the present invention is to provide a powder coating composition that after a single application and thermal curing can form a coating with good edge coverage and corner coverage. In addition, it is an object of the present invention that the composition after curing provides a film that has a combination of other physical properties such as good smoothness, flexibility (cupping), outdoor durability, chemical resistance and corrosion resistance.
[0016] These objects are at least partly achieved by a powder coating composition according to claim 1 .
[0017] Accordingly, a first aspect of the present invention relates to a powder coating composition comprising:
[0018] an acid-functional polyester resin A formed by reacting one or more polyol components with one or more polyacid components, wherein at least 90 mol % of the polyol component is neopentyl glycol and at least 87 mol % of the polyacid component is isophthalic acid (IPA), wherein the acid value (AN) of the polyester resin A is 20-90 mg KOH / g and the hydroxyl value is less than 50, preferably less than 15 mg KOH / g;
[0019] · a glycidyl-functional acrylic resin B having a weight average molecular weight of 2500-7000;
[0020] A curing catalyst C capable of catalyzing the reaction between the polyester resin A and the acrylic resin B;
[0021] · Optional β-hydroxyalkylamide D.
[0022] Surprisingly, it has been found that such powder coating compositions, after curing, can exhibit an excellent combination of physical properties, such as smoothness, flexibility, chemical resistance and corrosion resistance, and in particular, excellent edge coverage when tested according to the Low Voltage Wet Sponge test method (ASTM D5162), and / or excellent corner coverage when tested by the standard method for corner coverage of powder coatings (ASTM method D2967-7), even after only one coat is applied.
[0023] In a second aspect, the present invention relates to a method for providing a metal substrate having good edge coverage, comprising the steps of:
[0024] contacting an uncoated metal substrate having a surface and an edge with a single layer of the powder coating composition of the first aspect;
[0025] curing the powder coating composition,
[0026] Wherein the powder coating composition provides an edge coverage of at least 2.0 when tested by the low pressure wet sponge test method (ASTM D5162).
[0027] In a third aspect, the present invention relates to a method for preparing the powder coating composition of the first aspect, comprising the following steps:
[0028] Preparing acrylic resin B in a reactor;
[0029] Mixing the acrylic resin B with the catalyst C before or while it leaves the reactor to form a BC mixture; or
[0030] · mixing acrylic resin B with catalyst C by extrusion to form a BC mixture; or
[0031] Mixing acrylic resin B with catalyst C by dry blending to form a BC mixture;
[0032] Dry blending the BC mixture, polyester resin A and optional β-hydroxyalkylamide D to form a blend;
[0033] extruding the blend to form a homogenized mixture;
[0034] - Cool and grind the homogenized mixture.
[0035] In a fourth aspect, the present invention relates to an article, preferably an article having a metal substrate partially or fully coated with the powder coating composition of the first aspect or a powder coating composition prepared by the method of the third aspect.
[0036] After applying a layer of the coating composition of the present invention and curing, a smooth, high gloss surface can be obtained, thereby having good solvent resistance, flexibility, corrosion resistance and edge coverage.
[0037] In a fifth aspect, the present invention relates to a metal substrate prepared by the method of the second aspect of the present invention.
[0038] In a sixth aspect, the present invention relates to the use of the powder coating composition of the first aspect or the powder coating composition prepared by the method of the third aspect for providing a metal substrate with good edge coverage by a single layer, wherein the powder coating composition provides an edge coverage of at least 2.0 when tested by the low pressure wet sponge test method (ASTM D5162).
[0039] BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 Represents a metal test plate for ASTM D5162 testing, wherein the plate has a pinhole (1), a substrate 2, four faces: a top face (2), two side faces (3) and a bottom face (4), an edge (5) and four corners (6).
[0041] Figure 2 Represents a metal test block for use in ASTM method D2967-7 testing, wherein the block has corners (7) (only four are shown) and flat surfaces (8) (only two are shown).
[0042] "Resin" refers to a polymer having functional groups that is capable of being cured or crosslinked by a reaction involving its functional groups, induced by heat (thermosetting compositions) and / or radiation (radiation-curable compositions) to link the polymer chains together by forming permanent covalent (crosslinking) bonds, thereby producing a cured resin.
[0043] "Functional group" as used herein refers to a covalently bound atomic group within a molecule, such as a carboxylic acid group (-COOH), a hydroxyl group (-OH) or an oxirane (also known as a glycidyl) group, which is capable of reacting with a functional group of another molecule. For example, a carboxylic acid functional polyester resin contains a carboxylic acid functional group that is capable of reacting with a functional group of another molecule, such as a glycidyl epoxy acrylate resin containing a glycidyl group.
[0044] The terms "amorphous" and "crystalline" (sometimes including "semi-crystalline") used to characterize a resin or thermosetting powder coating composition are informal terms used in the art to indicate the main characteristic of the relevant resin or thermosetting powder coating composition in terms of its crystallinity. An amorphous resin has no melting temperature (Tm) because it melts within a certain temperature range, while a crystalline resin generally has a Tm. An amorphous resin is generally defined by its Tg. If a crystalline resin has a Tg, its Tg is lower than its Tm. "Tg" herein refers to the glass transition temperature. Tg is determined using differential scanning calorimetry (DSC) as described herein.
[0045] The curing of the thermosetting powder coating composition of the present invention is carried out using heat and can be referred to as "thermal curing", for example using infrared (IR) lamps. For clarity, the term "thermal curing" does not include radiation curing, such as ultraviolet (UV) or electron beam induced curing.
[0046] The curable thermosetting powder coating composition is applied to an object (eg, an article) and forms a film or coating on the substrate after heat curing. When the composition contains a pigment, such a coating is generally referred to as a paint layer.
[0047] The composition containing the functional resin and the curing catalyst (if present), wherein these functional resins are capable of reacting together to form a cured composition when cured (i.e., crosslinked), is generally referred to as the binder component of the coating composition. Other components (e.g., pigments, flow additives, etc.) may be added to the binder to form the final composition, which is applied to an object and forms a coating on the object after curing.
[0048] "Edge coverage" according to the present invention means covering the edge of a metal substrate by applying and curing a layer of a powder coating composition that provides an edge coverage of at least 2.0 when the composition is tested according to the low pressure wet sponge test method (ASTM D5162).
[0049] The "Low Pressure Wet Sponge Test Method" of the present invention is a test as described in ASTM D5162, wherein a single layer of powder coating is provided on a metal test panel. The test panel has four corners (6) and has edges (5) on four sides of the panel (top (2), bottom (4) and two side (3)) (see Figure 1 ). The edge thickness is about 0.5 mm. There is a hole (1) on the metal test plate for hanging and fixing the plate. The plate is suspended from a bracket by metal wires perpendicular to the bottom surface of the protective cover, which is standard procedure. The thickness of the powder coating after curing is an average of 50-125 μm. Discontinuities and pinholes on the edges (5) and corners (6) are detected using a pinhole detector, such as the DeFelsko PosiTestLPD pinhole detector, according to ASTM D5162, with the improvement that tap water is used instead of tap water and a low-foaming wetting agent.
[0050] The exposure of the substrate at edges and corners (i.e., discontinuities and pinholes) was rated as follows (the numbers in parentheses refer to Figure 1 Numbers in ):
[0051] 0.0 No coverage along the bottom (4), edges (5) of the sides (3), and no coverage at the corners (6) (very poor edge coverage)
[0052] 1.0 Some coverage along the edges (5) of the bottom (4) or sides (3), but no coverage along the edges of the top (2) and corners (6) (poor edge coverage)
[0053] 2.0 Full coverage along the edges (5) of the bottom (4), some coverage along the edges (5) of the sides (3), but no coverage at the corners (6) (good edge coverage)
[0054] 3.0 Full coverage of edges (5) along all four sides (2, 3, and 4), including all corners (very good edge coverage).
[0055] When the result is better than the lower level but still does not meet the requirements of the next level, an intermediate value (1.5, 2.5) can be assessed.
[0056] As used herein, the term "corner coverage" refers to the ratio of the average corner thickness of a test block coating to the average surface thickness of the test block coating as described in ASTM Method D2967-7 (2013) (Standard Test Method for Corner Coverage of Powder Coatings), with the improvement that the powder coating composition is sprayed onto a substrate (square test block) rather than immersing the substrate in a fluidized bed. "Corner coverage" is the ratio of the average corner thickness of a test block coating to the average surface thickness of a test block coating, expressed as a percentage, where surface coverage refers to the average corner thickness of a test block coating applied to each flat surface ( Figure 2 The coating thickness on (8)) in the figure is the thickness at the sharp 90° angle of the steel block ( Figure 2 (7)) The average thickness of the coating. It should be noted here that the term "corner" ( Figure 1 (6)) is similar to the term used in "corner coverage" (the sharp 90° corners of the block, Figure 2 The meaning in (7) is different. DETAILED DESCRIPTION OF THE INVENTION
[0058] Acid functional polyester resin A
[0059] The polyester resin A is acid functional, which means that the polyester contains terminal carboxylic acid groups. The acid functional polyester resin A is formed from one or more polyol components and one or more polyacid components, wherein at least 90 mol% of the polyol component is neopentyl glycol, and at least 87 mol% of the polyacid component is isophthalic acid (IPA); wherein the acid value (AN) of the polyester resin A is 20-90 mg KOH / g, and the hydroxyl value is less than 50, preferably less than 15 mg KOH / g.
[0060] The polyester resin A may also be referred to as "super durable polyester", which refers herein to a polyester containing at least 87 mol % of isophthalic acid based on the molar fraction of polyacid and at least 90 mol % of neopentyl glycol based on the molar fraction of polyol.
[0061] The polyester A containing carboxylic acid groups of the present invention is a polyester resin which is a carboxylic acid functional polyester. It can generally be obtained by: a) reacting a polyol with a diacid and / or an anhydride thereof to form a hydroxyl functional polyester, which is then reacted with a polycarboxylic acid and / or an anhydride thereof; or b) reacting all polyols with all dicarboxylic acids and polycarboxylic acids and / or their anhydrides in a single step.
[0062] The carboxylic acid-functional polyester resins A of the invention are preferably prepared by reacting all polyols with all dicarboxylic acids and polycarboxylic acids and / or their anhydrides in a single step.
[0063] The carboxylic acid group-containing polyester resin A of the present invention generally has an acid value of at least 20, preferably at least 30, more preferably at least 40 mgKOH / g. The acid value of the polyester resin A is generally at most 90, preferably at most 75, more preferably at most 60 mgKOH / g.
[0064] The hydroxyl value of the polyester resin A is less than 50, preferably less than 15, even more preferably less than 10 mg KOH / g. Surprisingly, it has been found that when the polyester resin A has a sufficiently low viscosity and such a low amount of residual OH functional groups, it is possible to achieve similar or better application properties and better flow properties than polyesters with higher hydroxyl values and viscosities (which result in lower flow properties and poorer appearance, thus requiring additional coats to achieve a good appearance). On the other hand, the coating composition of the present invention can simultaneously have good edge coverage and good appearance with only one coat.
[0065] The diacid component of polyester A is usually composed of 87-100 mol% of isophthalic acid and 0-13 mol% of other diacid components selected from the following: one or more aliphatic, alicyclic and / or aromatic diacids, such as terephthalic acid, fumaric acid, maleic acid, phthalic anhydride, CHDA, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, succinic acid, adipic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,12-dodecanedicarboxylic acid, undecanedioic acid, tridecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, heptadecanedioic acid, octadecanedioic acid, or the corresponding anhydrides, and any mixtures thereof. CHDA and adipic acid are most preferred.
[0066] Polybasic organic carboxylic acid refers to an organic compound containing at least 3 carboxylic acid groups. The polybasic organic acid can be used in the form of acid, anhydride, or a mixture of acid and anhydride. The polybasic organic acid of polyester A usually accounts for 0-10 mol% of the total acid and / or anhydride of polyester A. The polybasic organic acid is preferably selected from trimellitic acid, pyromellitic acid, trimellitic anhydride and pyromellitic anhydride, and any mixture thereof. Most preferably, trimellitic anhydride.
[0067] The polyol component of the polyester resin A contains at least 90 mol% of neopentyl glycol. The polyol component in the polyester resin A may contain other polyols having 2 OH groups, such as ethylene glycol, or other polyols having at least 3 OH groups, such as trimethylolpropane.
[0068] This diol can be 0-10 mol% of other diol components selected from the following: one or more aliphatic and / or alicyclic diols, such as ethylene glycol, diethylene glycol, 1,3-propylene glycol, propylene glycol, 1,4-butylene glycol, 1,6-hexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, 2-methyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, hydrogenated bisphenol A, hydroxypivalate of neopentyl glycol. Among them, 1,6-hexanediol is most preferred.
[0069] The polyol component having at least 3 OH groups of the polyester resin A usually accounts for 0-10 mol% of the total hydroxyl groups of the polyester resin A. The polyol component having at least 3 OH groups of the polyester resin A is preferably selected from glycerol, trimethylolpropane, trishydroxyethyl isocyanurate (THEIC), ditrimethylolpropane, pentaerythritol. Trimethylolpropane is most preferred.
[0070] Advantageously, the carboxylic acid functionality of the polyester resin A is greater than 1.2, preferably 1.4, more preferably 1.6.
[0071] Advantageously, the carboxylic acid functionality of polyester A is below 2.6, preferably 2.4, more preferably 2.2 (functionality is defined as the average number of acid groups per molecule, defined by "measured Mn" / (56100 / ANV), where ANV is the acid number).
[0072] The carboxylic acid functional polyester resin A of the present invention advantageously has a number average molecular weight (Mn), measured by gel permeation chromatography (GPC), of at least 1000, preferably at least 1500. The Mn of the polyester resin A is preferably at most 3000, more particularly at most 2500, measured by GPC (using polystyrene standards and tetrahydrofuran as eluent, measured at 35° C.).
[0073] The carboxylic acid functional polyester resin A of the present invention advantageously has a weight average molecular weight (Mw), measured by gel permeation chromatography (GPC), of at least 2500, preferably at least 4000. The Mw of the polyester resin A is preferably at most 11000, more particularly at most 8000, measured by GPC (using polystyrene standards and tetrahydrofuran as eluent, measured at 35°C).
[0074] Advantageously, the carboxylic acid-functional polyester resin A of the present invention is an amorphous polyester.
[0075] The carboxylic acid functional polyester resin A of the present invention advantageously has a glass transition temperature of 45-90°C, measured by differential scanning calorimetry (DSC) with a heating gradient of 10°C / min according to ASTM D3418. Preferably, the polyester resin A has a glass transition temperature below 70°C, more preferably below 63°C.
[0076] The carboxylic acid functional polyester resin A of the present invention advantageously has a Brookfield cone and plate viscosity of 500 to 10000 mPa.s, preferably 1200 to 2400 mPa.s, measured at 200°C according to ASTM D4287-88.
[0077] The polyester resin A of the present invention can be prepared by conventional esterification technology known in the art.
[0078] The polyesters are preferably prepared according to a process consisting of one or more reaction steps. For the preparation of these polyesters, a conventional reactor equipped with a stirrer, an inert gas (nitrogen) inlet, a thermocouple, a distillation column connected to a water-cooled condenser, a water separator and a vacuum connection is used. The esterification conditions for the preparation of the polyesters are conventional, i.e., standard esterification catalysts such as dibutyltin oxide, dibutyltin dilaurate, n-butyltin trioctoate, monobutyltin oxide, tin oxalate, sulfuric acid or sulfonic acid can be used in an amount of 0.0-0.50% by weight of the reactants, and optionally color stabilizers such as phosphonites and phosphite type stabilizers such as tributyl phosphite, triphenyl phosphite in an amount of 0-1% by weight of the reactants. The polyesterification is usually carried out at a temperature gradually increasing from 130° C. to about 190-250° C., first at atmospheric pressure or under pressure and then, if necessary, at the end of each process step under reduced pressure, while maintaining these operating conditions until a polyester with the desired hydroxyl and / or acid number is obtained. The degree of esterification is monitored by measuring the amount of water formed during the reaction and the properties of the resulting polyester (e.g. hydroxyl number, acid number and viscosity). Final additives (including catalysts) can be added to the reactor when the reactor is unloaded and / or added to the reactor during the powder coating preparation process, extrusion or mixing.
[0079] Glycidyl functional acrylic resin B
[0080] The glycidyl-functional acrylic resin B of the powder composition of the present invention has a weight average molecular weight of 2500-7000, measured by GPC (using polystyrene standards and tetrahydrofuran as eluent, measured at 35°C). Preferably, the glycidyl-functional acrylic resin B has a weight average molecular weight (Mw), measured by gel permeation chromatography (GPC), of at least 2500, preferably at least 4200. Preferably, the Mw of the glycidyl-functional acrylic resin B is at most 7000, more particularly at most 5500, measured by GPC (using polystyrene standards and tetrahydrofuran as eluent, measured at 35°C).
[0081] The glycidyl-functional acrylic resin B is preferably obtained by reacting glycidyl methacrylate and / or glycidyl acrylate, at least one (meth)acrylic monomer, and optionally an ethylenically monounsaturated monomer different from the glycidyl (meth)acrylate and the (meth)acrylic monomer. The (meth)acrylic monomer is selected from alkyl esters of α,β-ethylenically unsaturated carboxylic acids having the following molecular formula:
[0082]
[0083] wherein R1 is a hydrogen atom or a methyl group, and R2 represents an alkyl group having 1 to 18 carbon atoms, preferably 1 to 6 carbon atoms. Examples of (meth)acrylic monomers include alkyl esters of acrylic acid or methacrylic acid, such as ethyl acrylate, butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate and lauryl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobutyl methacrylate and lauryl methacrylate.
[0084] The ethylenically monounsaturated monomers which may be used optionally are preferably selected from styrene, vinyltoluene, dimethylstyrene, α-methylstyrene, hydroxyethyl acrylate or methacrylate, hydroxypropyl acrylate or methacrylate, acrylonitrile, acrylamide, vinyl acetate, etc., which may be used alone or as a mixture. The glycidyl-containing acrylic copolymer B is preferably obtained from about 27-47 wt % of glycidyl methacrylate and / or glycidyl acrylate (preferably glycidyl methacrylate), about 73-53 wt % of (meth)acrylic monomers (preferably methyl and n-butyl methacrylate) and about 0-20 wt % of other ethylenically monounsaturated monomers (preferably styrene), the weight % being relative to the total reaction mixture for preparing the glycidyl-containing acrylic copolymer B. These acrylic copolymers are prepared by known polymerization methods, such as bulk polymerization, emulsion polymerization or solution polymerization in an organic solvent. The monomers are copolymerized in the presence of a free radical initiator such as benzoyl peroxide, tert-butyl peroxide, decanoyl peroxide, azobisisobutyronitrile, etc., and the amount of the free radical initiator used is 0.1-7.0% by weight of the monomers.
[0085] The preferred glycidyl-functional acrylic resin B of the present invention advantageously has a number average molecular weight (Mn), determined by gel permeation chromatography (GPC), of at least 1000, preferably at least 1500. The Mn of the glycidyl-containing acrylic copolymer B is preferably at most 2500, more particularly at most 2000, determined by GPC (determined at 35° C. using polystyrene standards and tetrahydrofuran as eluent).
[0086] In order to better control the molecular weight and its distribution, a chain transfer agent may be added during the polymerization process, preferably one of the following: mercaptans, such as n-dodecyl mercaptan, tert-dodecyl mercaptan, isooctyl mercaptan, etc., halides, such as carbon tetrabromide, disulfide or thioether, etc. The amount of the chain transfer agent is 0-10% by weight of the monomers used for the copolymerization.
[0087] The glycidyl-functional acrylic resin B of the present invention generally has an epoxide equivalent weight (EEW) of at least 280, preferably at least 320, more preferably at least 360 g / epoxide equivalent. The glycidyl-containing acrylic copolymer B generally has an epoxide equivalent weight (EEW) of at most 500, preferably at most 450, more preferably at most 400 g / epoxide equivalent.
[0088] The glycidyl-functional acrylic resin B of the present invention advantageously has a glass transition temperature of 35-60° C., measured by differential scanning calorimetry (DSC) with a heating gradient of 10° C. / min according to ASTM D3418. Preferably, the glass transition temperature of the glycidyl-containing acrylic copolymer B is above 40° C., more preferably above 42° C.
[0089] The glycidyl-functional acrylic resin B of the present invention advantageously has a Brookfield cone and plate viscosity of 10,000 to 75,000 mPa.s, preferably 15,000 to 55,000 mPa.s, measured at 150° C. according to ASTM D4287-88.
[0090] One example of a commercially available glycidyl-functional acrylic resin B is Almatex PD 3402 from Anderson Development Company, but many more are available from companies such as DIC, Estron, and Allnex.
[0091] Advantageously, the glycidyl-functional acrylic resin B has a functionality of at least 2.5, preferably at least 4 and at most 8.5, preferably at most 7.0 (functionality is defined as the average number of glycidyl groups per molecule, expressed as "measured Mn" / EEW).
[0092] Catalyst C
[0093] The curing catalyst C is capable of catalyzing the reaction between the polyester resin A and the acrylic resin B. The curing catalyst C is generally a thermosetting curing catalyst and may be selected from amines, imidazoles, phosphines, ammonium salts, phosphonium salts, blocked amine or phosphine catalysts, coated catalysts, and combinations thereof, preferably a combination of an aryl phosphonium halide with imidazole and a tertiary amine, more preferably a combination of ethyltriphenylphosphonium bromide (BETP) with 2-methylimidazole and tributylamine.
[0094] The total wt% of the curing catalyst C in the powder coating composition is 0.2-1.3 wt% relative to the total weight of the powder coating composition.
[0095] Advantageously, the total % of curing catalyst C is at least 0.2%, preferably at least 0.3% and at most 1.3%, preferably at most 1.2%.
[0096] When a combination of catalysts is used, the ratio between the 3 catalysts may be between 0 / 0 / 100 - 0 / 100 / 0 and 100 / 0 / 0.
[0097] The catalyst C can be mixed before or while the polyester resin A or the glycidyl-functional acrylic resin B leaves the synthesis reactor or during preliminary mixing or extrusion, but the catalyst C is preferably mixed with the glycidyl-containing acrylic copolymer B.
[0098] Optional β-hydroxyalkylamide D
[0099] Optionally, a β-hydroxyalkylamide is added to the powder coating composition. The β-hydroxyalkylamide comprises at least one, preferably two, bis(β-hydroxyalkyl)amide groups. More preferred β-hydroxyalkylamides are those available from EMS under the trade names Primid XL552, Primid QM1260 and Primid SF 4510, and those described in US4727111, US4788255, US54076917, EP0322834 and EP0473380.
[0100] For Primid XL552, typical hydroxyamide values are 600-725 mg KOH / g, and equivalent weights are 94-77 g / hydroxyamide group.
[0101] Advantageously, the ratio of the combination of the equivalents of glycidyl-functional acrylic resin B (the number of moles of glycidyl groups in resin B) and, if present, the number of moles of hydroxyamide groups of the β-hydroxyalkylamide to the equivalents of carboxylic acid groups of the polyester resin A (the number of moles of carboxylic acid groups in resin A) is from 33 / 67 to 67 / 33, preferably from 45 / 55 to 55 / 45.
[0102] The ratio of the equivalent of glycidyl groups in the glycidyl-containing acrylic copolymer B (the number of moles of glycidyl groups in the acrylic resin B) to the moles of hydroxyamide groups of the (optional) β-hydroxyalkylamide D (the number of moles of hydroxyalkylamide groups in the β-hydroxyalkylamide D) is 100 / 01 to 40 / 60, preferably 75 / 25 to 50 / 50. The powder coating composition may contain additional components.
[0103] In addition to the above-mentioned components, the composition of the invention may also contain one or more components such as carboxyl-containing semi-crystalline polyesters as additives, the content of which is usually less than 5% of the powder coating composition. Carboxyl-containing crystalline or semi-crystalline polyester resins are those based on polycarboxylic acids and polyols. Polycarboxylic acids are, for example, linear aliphatic dicarboxylic acids with 2 to 22 methylene groups and / or terephthalic acid / isophthalic acid, the content of which is at least 85 mol %, based on the total amount of all polycarboxylic acids used. As polyols, for example (cyclo)aliphatic alcohols, especially with 2 to 10 C atoms, can be used.
[0104] Other components include flow control agents such as P 896, P 824, P 6000 (ALLNEX), P-67 and PV5 (ESTRON), 4F, LR8820(BASF), BYK360 and 361 (BYK Chemie), degassing agents such as benzoin (BASF), fillers, UV absorbers such as 900 (BASF), hindered amine light stabilizer such as 144 (BASF), other stabilizers such as 312 and 1130 (BASF), antioxidants such as 1010 (BASF), and stabilizers of the phosphonite or phosphite type such as 168(BASF), 626(SI GROUP), 613 (DOVER) or P-EPQ(CLARIANT), pigments, fillers and dyes.
[0105] Both colored and transparent paints can be prepared. A variety of dyes, fillers and pigments can be used in the composition of the present invention. Examples of useful pigments, fillers and dyes are metal oxides such as titanium dioxide, iron oxide, zinc oxide, etc., metal hydroxides, metal powders, sulfides, sulfates, carbonates, silicates such as ammonium silicate, carbon black, talc, china clay, barite, iron blue, lead blue, organic red, organic maroon, etc.
[0106] The powder compositions generally contain less than 40% of these additional components, based on the total powder coating.
[0107] Preferably, the powder coating composition has a gel time measured at 200°C of less than 100 seconds, preferably 20-50 seconds.
[0108] The components of the composition of the present invention can be mixed by dry blending in a mixer or a blender (e.g., a drum mixer). The premix is then typically homogenized at a temperature of 50-120° C. in a single screw extruder (e.g., BUSS-Ko-Kneter) or a twin screw extruder (e.g., PRISM or Werner & Pfleiderer ZSK). The extrudate is typically ground into a powder having a particle size of 10-150 μm after cooling. The powder composition can be deposited on a substrate using a powder gun (e.g., an electrostatic CORONA spray gun or a friction charging TRIBO spray gun). On the other hand, well-known powder deposition methods, such as fluidized bed technology, can also be used. After deposition, the powder is typically heated by different heating methods (including infrared) to a temperature of 140-220° C., preferably about 180-200° C., for 10-30 minutes, so that the particles flow and fuse together to form a smooth, uniform, continuous, pit-free coating on the surface of the substrate.
[0109] In one embodiment, the powder coating composition provides a good edge coverage rating (2.0) or a very good edge coverage rating (3.0) or any level between these ratings.
[0110] In another embodiment, the powder coating composition provides a corner coverage of 10% or more, preferably 15% or more, more preferably 20% or more.
[0111] The powder composition of the present invention can provide excellent flow properties and allow obtaining glossy coatings, excellent edge coverage in a single coat, excellent mechanical properties and solvent resistance.
[0112] The present invention also relates to a method for providing good edge coverage of a metal substrate, comprising the steps of:
[0113] contacting an uncoated metal substrate having a surface and edges with a single layer of a powder coating composition as described above, and
[0114] curing the powder coating composition;
[0115] Wherein the powder coating composition provides an edge coverage of at least 2.0 when tested using the low pressure wet sponge test method (ASTM D5162).
[0116] Preferably, curing occurs at a temperature of 160-210°C, more preferably 180-200°C, for 10-30 minutes, preferably 10-15 minutes.
[0117] In one embodiment, the thickness of the single layer after curing is 50-125 μm.
[0118] The invention also relates to a metal substrate coated by the method.
[0119] The present invention also relates to a method for preparing a powder coating composition, comprising the following steps:
[0120] Preparing acrylic resin B in a reactor;
[0121] Mixing acrylic resin B with catalyst C before or while leaving the reactor to form a BC mixture; or
[0122] · mixing acrylic resin B with catalyst C by extrusion to form a BC mixture; or
[0123] Mixing acrylic resin B with catalyst C by dry blending to form a BC mixture;
[0124] Dry blending the BC mixture, polyester resin A and optional β-hydroxyalkylamide D to form a blend;
[0125] extruding the blend to form a homogenized mixture;
[0126] - Cool and grind the homogenized mixture.
[0127] The present invention also relates to an article, which generally has a metal substrate, which is partially or fully coated with a powder coating composition as described above or with a powder coating composition prepared by a method as described above.
[0128] The present invention also relates to the use of a powder coating composition as described above, or a powder coating composition prepared by a method as described above, for providing good edge coverage of a metal substrate by application of a single layer, wherein the powder coating composition provides an edge coverage of at least 2.0 when tested by the low pressure wet sponge test method (ASTM D5162).
[0129] method
[0130] 1. Acid value AN
[0131] Accurately weigh a certain amount of resin and place it in a 250ml conical flask. Then add 50-60ml of tetrahydrofuran. Slightly heat the solution until the resin is completely dissolved, and make sure the solution does not boil. Cool the solution to room temperature, then add 3 drops of phenolphthalein, and then titrate with standard potassium hydroxide to the endpoint. The acid value is calculated as follows:
[0132] Acid value (mg KOH / g) = ml x N*56,1 / g
[0133] g = mass of resin
[0134] N = normal concentration of potassium hydroxide solution
[0135] 2. Viscosity
[0136] The viscosity is determined according to ASTM D 4287 using a Brookfield CAP2000 (variable speed) viscometer for determining the viscosity of high viscosity polyesters. The desired temperature and speed are selected. A small amount of the resin sample is placed on a heated plate so that when the cone is lowered, a small amount of excess resin spreads to the sides. The spindle rotation is started. The sample is thoroughly degassed by raising and lowering the cone several times while stopping the cone rotation button. Once completely degassed, a reading can be taken. This process is repeated until a repeatable, highly stable reading is obtained.
[0137] 3. Determination of Tg by DSC
[0138] The Tg values reported here are the midpoint Tg determined at the slope point of the DSC curve. The DSC curves were determined using a heating rate of 10°C / min.
[0139] 4. Determination of molecular weight by GPC
[0140] The weight average molecular weight, number average molecular weight and molecular weight distribution of the polymers were determined by gel permeation chromatography (GPC) on a HPLC Perkin-Elmer equipped with a refractive index (RI) detector, using HPLC grade tetrahydrofuran as the eluent, a temperature of 35°C, three PLgel columns 100-1000-10000A (300x7.8mm) 5um, Polymer Standard Service (PSS) using polystyrene standards (Mw of 162-96000 Daltons), and toluene was added to each sample as a mobile marker peak.
[0141] 5. Functionality
[0142] The functionality is defined as the average number of acid groups or glycidyl groups per molecule calculated by Mn / (56100 / AN) or Mn / EEW.
[0143] 6. Epoxy Equivalent Weight (EEW)
[0144] The epoxy equivalent weight is the weight of an epoxy compound containing exactly one mole of glycidyl groups, expressed in g / mol.
[0145] Accurately weigh the resin equivalent to 0.7-0.8 milliepids of epoxy equivalents and place it in a 250 ml conical flask. Then add 20 ml of dichloromethane. Slightly heat the solution until the resin is completely dissolved, making sure the solution does not boil. Cool the solution to room temperature. Then, use a measuring cylinder to add about 0.5-1 g of tetraethylammonium bromide powder and 4-6 drops of crystal violet indicator (the color changes from blue to green).
[0146] Then, the mixture was immediately titrated with 0.1 N perchloric acid solution under magnetic stirring until the endpoint was reached.
[0147] calculate
[0148] Epoxy equivalent weight = (P*1000) / ((V-Vo)*N)g / epoxy equivalent
[0149] in
[0150] V = ml of 0.1N perchloric acid solution used to titrate the sample
[0151] Vo = ml of 0.1N perchloric acid solution used to titrate the blank solution
[0152] N = perchloric acid equivalent concentration
[0153] P = sample weight, expressed in g
[0154] 7. Hydroxyl value OHV
[0155] The hydroxyl value (OHV) is defined as the amount of KOH mg corresponding to the amount of acetic acid esterified after acetylation of the hydroxyl groups of 1 g of sample (reference method DIN 53240)
[0156] Acetylation mixture: Dilute 15 g of acetic anhydride with analytical grade pyridine in a 250 ml Erlenmeyer flask.
[0157] The determination must be performed twice and a blank test must be completed according to the procedure reported below.
[0158] Add 20 ml of the acetylation mixture to the accurately weighed sample based on the expected hydroxyl value in the flask. Insert an air cooler and place the flask in a constant temperature bath at 100°C and reflux for 1 hour. Then add 30 ml of tetrahydrofuran to thoroughly rinse the air cooler, followed by 10 ml of distilled water. After vigorous shaking, place the solution in the constant temperature bath again for 10 minutes. After removing the flask from the constant temperature bath, add another 30 ml of tetrahydrofuran. After shaking the flask again, allow the solution to cool.
[0159] Indicator solution: Dissolve 0.80 g thymol blue and 0.25 g cresol red in 1 L methanol.
[0160] The OHV is determined by manually titrating the prepared cold blank and sample flasks with standardized 0.5N methanolic potassium hydroxide solution using 10 drops of indicator solution. The endpoint is reached when the color changes from yellow to gray to blue and remains blue for 10 seconds. The hydroxyl value is then calculated according to the following formula:
[0161] Hydroxyl value = (BS) x N x 56.1 / M + AN
[0162] in:
[0163] B = ml of KOH used for blank titration
[0164] S = ml of KOH used for sample titration
[0165] N = normal concentration of potassium hydroxide solution
[0166] M = sample weight (base resin)
[0167] AN = acid value of the sample, in mg KOH / g
[0168] 8. Determination of gelation time
[0169] Determine the time required for the test sample to change from a liquid (melt) to a solid-gel state (gel):
[0170] This time is called the "gel time". The finished coating or resin and appropriate hardener can be tested
[0171] Physical blends (DIN 55990, part 8, ISO 8130-6).
[0172] Preheat the test plate to the test temperature. Place a spoonful of about 0.9 g of the powder paint test sample into one of the grooves (cavities) of the test plate. Start the stopwatch and immediately stir the test sample gently and continuously in a circular motion with a metal pen until the melt viscosity begins to increase noticeably. By lifting the metal pen vertically, if the strands of material break easily, the material is judged to have gelled: stop the stopwatch at this time.
[0173] The total time (in seconds) to the end of the test (when gelation occurs) at the specified test temperature represents the measurement result. Example
[0174] Example 1: Polyester A
[0175] 425 parts of neopentyl glycol are placed in a conventional four-necked round bottom flask equipped with a stirrer, a distillation column connected to a water-cooled condenser, a nitrogen inlet and a thermometer connected to a temperature regulator. The contents of the flask are heated to a temperature of about 140°C while stirring under nitrogen, at which time 721 parts of isophthalic acid and 1 part of monobutyltin oxide are added. The reaction is continued at atmospheric pressure and 240°C until about 95% of the theoretical amount of water has been distilled off and a clear carboxyl-functionalized prepolymer is obtained. 0.6 parts of triphenyl phosphite are added to the first step polyester at 200°C and a vacuum of 50 mm Hg is gradually applied at a temperature of 235°C. Once the target acid number and viscosity are reached, the polyester is cooled to 200°C and 0.3 parts of BETP are added. After 60 minutes the following characteristics are obtained:
[0176] Acid ester: 35mg KOH / g
[0177] Brookfield (lamina) viscosity: 2000mPa.s, 200℃
[0178] Tg(DSC):61℃
[0179] Hydroxyl value OHV: 4.5mg KOH / g
[0180] Molecular weight distribution: Mn 2363 / Mw 6245
[0181] Functionality: 1.5
[0182] Example 2: Glycidyl-containing acrylic copolymer B
[0183] 500 parts of ethyl acetate were introduced into a reactor equipped with a thermocouple, a stirrer, a reflux condenser and a dropping funnel and heated to reflux temperature. A mixture consisting of 178 parts of glycidyl methacrylate, 173 parts of methyl methacrylate, 70 parts of butyl methacrylate, 47 parts of styrene, 14 parts of n-dodecyl mercaptan and 17 parts of 2,2-azobis(2-methylpropionitrile) was added through a dropping funnel over 5 hours. After the addition was completed, the reaction mixture was boiled and refluxed for 1 hour. Then, 10 parts of 2,2-azobis(2-methylpropionitrile) were added and the reaction mixture was refluxed for another 2 hours. The solvent was distilled off under reduced pressure and the glycidyl-containing acrylic copolymer was collected. The acrylic copolymer thus obtained is a solid product that is easily ground into a white powder. It has the following characteristics:
[0184] Epoxy equivalent weight: 400g / epoxy equivalent
[0185] Brookfield (lamina) viscosity: 50000mPa.s, 150℃
[0186] Tg(DSC)51℃
[0187] Molecular weight distribution: Mn 2120 and Mw 5845
[0188] Functionality: 5.3
[0189] As Example 3, a glycidyl-containing acrylic resin prepared in a similar manner and based on glycidyl methacrylate, methyl methacrylate, butyl methacrylate and styrene and sold under the trade name Almatex PD 3402 was used.
[0190] Epoxy equivalent weight: 380g / equivalent
[0191] Brookfield (lamina) viscosity: 19000mPa.s, 150℃
[0192] Tg(DSC)46℃
[0193] Molecular weight distribution: Mn 1732, Mw 4612
[0194] Functionality: 4.6
[0195] The polyester and glycidyl-containing acrylic resin shown above were then formulated into powders according to the formulation described below.
[0196] Black paint preparation
[0197]
[0198] The table below gives the binder composition of different powder formulations.
[0199] First, the powder is prepared: the different solid components are dry mixed in a bag, and then the melt is homogenized using a ZSK-30P extruder at an extrusion temperature of about 90°C and a speed of 600 rpm. The homogenized mixture is then cooled and ground with a Vortisiv. The powder is then sieved to obtain a particle size of less than 200um. The powder thus obtained is deposited on MDF or Q-Panel CRS 0.05×7.5×12.5cm by electrostatic deposition using a GEMA-Optiflex-2 spray gun. When the film thickness is 50-140um, the board is placed in an electrically heated oven for curing, and unless otherwise stated, the curing is carried out at a target temperature of 180°C for 15 minutes. Table 1 lists the composition (components and amounts by weight) of different polyesters, and Table 2 lists the molar percentages of diols and acids.
[0200] Table 1
[0201] Example 1 Example 4 Example 5 Comparative Example Neopentyl glycol 424.5 374.1 414.9 406.1 1,6-Hexanediol 0.0 24.7 0.0 0.0 Trimethylolpropane 0.0 11.3 0.0 58.1 CHDA 0.0 72.9 0.0 0.0 Trimellitic anhydride 0.0 15.7 0.0 76.2 Isophthalic acid 721.4 627.9 728.2 593.1 Tributylamine 0.0 4.9 0.0 4.9 BETP 0.3 0.0 0.0 0.0 Yield 1000 1000 1000 1000 Number average molecular weight 2363 2098 1603 2846 Weight average molecular weight 6245 7645 4226 15128 Functionality (F) 1.5 1.9 1.4 1.5 Acid value (AN) 35 50 50 28.8 Viscosity at 200℃, mPa.s 2000 1800 1280 2420 Glass transition temperature (Tg, ℃) 61 52 59 59 Hydroxyl Value (OHV) 4.5 5.4 6.2 62.1
[0202] Table 2
[0203] mol% Example 1 Example 4 Example 5 Comparative Example Neopentyl glycol 100 92.5 100 90.0 1,6-Hexanediol 0.0 5.4 0.0 0.0 Trimethylolpropane 0.0 2.2 0.0 10.0 CHDA 0.0 9.9 0.0 0.0 Trimellitic anhydride 0.0 1.9 0.0 10.0 Isophthalic acid 100 88.2 100 90.0
[0204] The composition of the powder coatings is shown in Table 3. Curing of the single coat was carried out at a target temperature of 200°C for 10 minutes.
[0205] Table 3
[0206]
[0207] 2-Methylimidazole was obtained from Aalchem under the trade name AHA 6312
[0208] TGIC is triglycidyl isocyanurate, obtained from Niutang, trade name Nuitang TGIC-G
[0209] Benzoin from Akros Organics
[0210] Carbon black was obtained from Cabot under the trade name Black Pearls 800
[0211] The coating characteristics of the finished coatings obtained with the binder of the invention (PC1, PC2) and the comparative (CPC1) are given in Table 4.
[0212] Table 4
[0213] OK PC1 PC2 CPC1 1 Gel time (s) DIN 55990 Part 8 30 44 47 2 Inclined plate flow(mm) PCI#7 29 36 46 3 Smoothness@100μm PCI#20 5-6 4 6 4 Glossiness (unit): 60° / 20° ASTM D523 95 / 76 97 / 83 91 / 62 5 DOI ASTM D523 35.5 45 25.1 6 Impact resistance direct / indirect ASTM D2794 0 / 0 60 / 100 20 / 20 7 Flexibility ASTM D522 0.8 0.125 0.125 8 Chemical resistance PCI#8 By (4) By (4) By (4) 9 Edge coverage (67.5V, 80kΩ) ASTM D5162 2.5 2.5 0
[0214] Row 1: Gel time measured at 200°C
[0215] Row 2: represents the sheet flow of the powder coating measured at 180°C (in mm): The Complete Finisher's Handbook, page 451, 4th edition, published by The Powder Coating Institute in 2012.
[0216] Row 3: represents the visual assessment of a powder coating at 100 μm thickness, where 10 represents a very smooth high gloss coating and 1 represents a strong orange peel coating with reduced 60° gloss value: The Complete Finisher's Handbook, pages 452-453, 4th edition, published by The Powder Coating Institute in 2012.
[0217] Row 4: represents the gloss of the powder coating at 60° and 20° tested according to ASTM D523.
[0218] Row 5: represents the image discrimination (DOI) according to ASTM D523: higher values indicate better coating appearance.
[0219] Row 6: Direct / indirect impact strength measured according to ASTM D 2794. The maximum impact force (in kg.cm) at which the coating does not break is recorded.
[0220] Row 7: represents the Erichsen cupping measured according to ASTM D522.
[0221] Row 8: shows the MEK resistance measured on 100 μm of the powder coating, which corresponds to the appearance of the cured film surface after 50 double rubs (back and forth) with a cotton pad soaked in aggressive MEK (1 = poor, up to 4 = excellent): The Complete Finisher's Handbook, pages 484-485, 4th edition, published by The Powder Coating Institute in 2012.
[0222] Row 9: represents the edge coverage determined using the sponge test method according to ASTM D5162 as described above.
[0223] The powders according to the invention (PC1 and PC2) give monocoats with very good edge coverage compared to a reference based on the same resins as in Example 1 but with TGIC (triglycidyl isocyanurate) instead of the combination of glycidyl-containing acrylic resin B and β-hydroxyalkylamide D.
[0224] In order to understand the effect of different percentages of curing catalyst on the sponge test results, PC1 and PC2 with additional amounts of 0-1% BETP were prepared, thereby obtaining PC3 which is PC1 with 0.5% BETP added, PC4 which is PC1 with 1% BETP added instead of 0.75%, PC5 which is PC2 with 0.35% BETP added, PC6 which is PC2 with 0.5% BETP added instead of 0.75%, and CPC3 which is PC2 without BETP. The results after curing at 180°C for 15 minutes are reported in Tables 5 and 6.
[0225] Table 5
[0226] CPC2 PC3 PC1 PC4 BETP added% 0 0.5 0.75 1.0 Gel time, 200℃(s) DIN 55990 Part 8 54 37 29 27 Inclined plate flow(mm) PCI#7 41 33 29 27 Smoothness@100μm PCI#20 6 6 6 4-5 Gloss (unit): 60° / 20° ASTM D523 96 / 94 98 / 83 97 / 79 95 / 72 DOI ASTM D523 64.6 44.1 35.5 30.5 Flexibility ASTM D522 0.167 0.8 0.8 0.167 Edge coverage (67.5V, 80kΩ) ASTM D5162 1.5 2 2.5 2
[0227] Table 6
[0228]
[0229]
[0230] Based on the results reported in Tables 5 and 6, it was surprisingly found that the powder coating needed to contain at least 0.35% BETP to meet the required edge coverage rating, while CPC2 and CPC3 without BETP had poor edge coverage.
[0231] Table 7
[0232] PC2 PC2 PC2 Curing time 200℃*10min 180℃*10min 180℃*15min Gel time, 200℃(s) DIN 55990 Part 8 44 44 44 Inclined plate flow(mm) PCI#7 36 36 36 Smoothness@100μm PCI#20 4 4 4 Gloss (unit): 60° / 20° ASTM D523 97 / 86 97 / 79 97 / 83 DOI ASTM D523 47.1 36.6 45 Impact resistance ASTM D2794 60 / 120 40 / 60 60 / 100 Flexibility ASTM D522 0.125 0.125 0.125 Chemical resistance PCI#8 By (4) By (4) By (4) Edge coverage (67.5V, 80kΩ) ASTM D5162 2 2.5 2.5
[0233] When tested at different times and temperatures, PC2 showed that a cure time between 180-200°C and 10-15 minutes provided very good edge coverage.
[0234] Additional tests were performed to verify the effect of the percentage of pigment in the black and white powder coatings reported in Table 8.
[0235] Table 8
[0236]
[0237]
[0238] This had no impact on the excellent edge coverage rating as shown in Table 9. This result was accompanied by the same good flexibility, smoothness and good chemical resistance.
[0239] Table 9
[0240]
[0241] From the test results of PC2, we also confirmed that the edge coverage determined by ASTM D5162 is a good predictor of the corner coverage determined by ASTM D2967-7, which confirms that when the percentage of thickness at the corner of the block is at least 15% of the thickness measured on the flat surface of the block
[0242] In addition, after 500 hours of salt spray resistance test based on ASTM B117 evaluated according to ASTM D1654 Procedure C, the creep increase of PC2 edge was only 0.5mm, while the creep increase of less than 20mm and less than 5mm in the best case can confirm good corrosion resistance.
[0243] The polyester of Example 5 in Table 1 was tested in a white powder coating and compared to powder coatings of the polyester of Example 4 and a comparative polyester.
[0244] Table 10
[0245]
[0246] Table 11
[0247] PC7 PC8 contrast Gel time, 200℃(s) DIN 55990 Part 8 33 32 30 Inclined plate flow(mm) PCI#7 30 29 40 Smoothness@100μm PCI#20 4 5 4 Gloss (unit): 60° / 20° ASTM D523 96 / 69 92 / 58 91 / 52 DOI ASTM D523 26.5 18.4 13.4 Flexibility ASTM D522 0.125 0.625 0.625 Chemical resistance PCI#8 By (4) By (3) By (3) Edge coverage (67.5V, 80 kΩ) ASTM D5162 2.5 2.5 1
[0248] As can be seen in Table 11, even though the Tg is increased compared to Example 4, the powder coating based on the polyester of Example 5 still exhibits excellent edge coverage.
[0249] In addition, Table 11 shows that the edge coverage of the comparative examples with OH values greater than 50 is much lower than that of the other coatings. In addition, the degree of differentiation of images (DOI) is the lowest among all.
[0250] Table 12
[0251]
[0252] Tables 12 and 13 report a comparison between two different glycidyl-containing acrylic resins, wherein the powder coating based on the glycidyl-containing acrylic resin of Example 2 was also able to provide good edge coverage.
[0253] Table 13
[0254] PC7 PC9 Gel time (s) DIN 55990 Part 8 33 27 Inclined plate flow(mm) PCI#7 30 27 Smoothness@100μm PCI#20 4 3 Gloss (unit): 60° / 20° ASTM D523 96 / 69 95 / 64 DOI ASTM D5239 26.5 20.7 Flexibility ASTM D522 0.125 0.625 Chemical resistance PCI#8 By (4) By (4) Edge coverage (67.5V, 80kΩ) ASTM D5162 2.5 2.5
[0255] 1507 parts of the GMA acrylic resin of Example 3 were dry blended with 74 parts of BETP in a bag and then melt homogenized at an extrusion temperature of about 90° C. and a speed of 600 rpm, then cooled and ground (Example 8).
[0256] Table 14
[0257]
[0258] Table 15
[0259] PC7 PC10 Gel time (s) DIN 55990 Part 8 33 41 Inclined plate flow(mm) PCI#7 30 34 Smoothness@100μm PCI#20 4 4 Gloss (unit): 60° / 20° ASTM D523 96 / 69 95 / 72 DOI ASTM D523 26.5 30 Impact resistance ASTM D2794 20 / 60 40 / 60 Flexibility ASTM D522 0.125 0.125 Edge coverage (67.5V, 80kΩ) ASTM D5162 2.5 2.5
[0260] Table 15 shows that mixing Catalyst C and Acrylic Resin B in the extruder to form a BC mixture can provide a composition with better flow and a coating with better impact resistance compared to mixing Polyester A, Acrylic Resin B and Catalyst C during extrusion.
Claims
1. A powder coating composition comprising: an acid-functional polyester resin A formed by reacting one or more polyol components with one or more polyacid components, wherein at least 90 mol % of the polyol component is neopentyl glycol, at least 87 mol % of the polyacid component is isophthalic acid (IPA), and wherein the polyester resin A has an acid value (AN) of 20-90 mg KOH / g and a hydroxyl value of less than 50, preferably less than 15 mg KOH / g; a glycidyl-functional acrylic resin B having a weight average molecular weight of 2500-7000 as determined by gel permeation chromatography (GPC) using polystyrene standards; a curing catalyst C capable of catalyzing the reaction between the polyester resin A and the acrylic resin B; and · Optional β-hydroxyalkylamide D.
2. The powder coating composition according to claim 1, a. wherein the content of polyester resin A is 70-98.8wt%, b. wherein the content of acrylic resin B is 1-30wt%, c. wherein the content of the curing catalyst C is 0.2-1.3wt%, d. wherein the content of β-hydroxyalkylamide D is 0-5wt%, The wt % is based on the total weight of the powder coating composition.
3. A powder coating composition according to claim 1 or 2, wherein the ratio of the combination of the equivalents of glycidyl groups of the acrylic resin B (the number of moles of glycidyl groups in the resin B) and the moles of hydroxyamide groups of the optional β-hydroxyalkylamide D to the equivalents of carboxylic acid groups of the polyester resin A (the number of moles of carboxylic acid groups in the polyester resin A) is 33 / 67-67 / 33, preferably 45 / 55-55 / 45.
4. A powder coating composition according to any one of claims 1 to 3, wherein the ratio of the equivalent of glycidyl groups of the acrylic resin B (the number of moles of glycidyl groups in the acrylic resin B) to the number of moles of hydroxyamide groups of the optional β-hydroxyalkylamide D is 100 / 1-40 / 60, preferably 75 / 25-50 / 50.
5. The powder coating composition according to any one of claims 1 to 4, comprising: a. 75-83wt% polyester resin A, b. 12-22 wt% of acrylic resin B, c. 0.3-1.2 wt% of curing catalyst C, d. 2-3.5 wt% of β-hydroxyalkylamide, The wt % is based on the total weight of the powder coating composition.
6. The powder coating composition according to any one of claims 1 to 5, wherein the polyester component A has one or more of the following properties: a. the acid value of the polyester resin A is at least 20, preferably at least 30, more preferably at least 40 mg KOH / g, and the acid value of the polyester resin A is at most 90, preferably at most 75, more preferably at most 60 mg KOH / g; b. The hydroxyl value of the polyester resin A is less than 10 mg KOH / g; c. the number average molecular weight (Mn) of the polyester resin A is at least 1000, preferably at least 1500, as determined by gel permeation chromatography (GPC); d. the number average molecular weight (Mn) of the polyester resin A is at most 3000, preferably at most 2500, as determined by gel permeation chromatography (GPC); e. The polyester resin A is an amorphous resin and preferably has a glass transition temperature of 30-90°C, preferably at least 45°C, as measured by differential scanning calorimetry (DSC) with a heating gradient of 10°C / min according to ASTM D3418; f. The functionality of the polyester resin A is at least 1.2, preferably at least 1.4, more preferably at least 1.6, wherein the functionality is defined as the average number of acid groups per molecule, calculated by "measured Mn" / (56100 / ANV); g. The functionality of the polyester resin A is at most 2.6, preferably at most 2.4, more preferably at most 2.2, wherein the functionality is defined as the average number of acid groups per molecule, calculated by "measured Mn" / (56100 / ANV); h. The diol component of the polyester resin A is composed of 90-100 mol% of neopentyl glycol and 0-10 mol% of other polyols; i. The diol component of the polyester resin A is composed of 90-100 mol % of neopentyl glycol and 0-10 mol % of other diol components selected from the following: One or more aliphatic and / or alicyclic diols, such as ethylene glycol, diethylene glycol, 1,3-propanediol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, 2-methyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, hydrogenated bisphenol A, hydroxypivalate of neopentyl glycol, preferably, the other diol components include 1,6-hexanediol; j. The diacid component of the polyester resin A consists of 87-100 mol% of isophthalic acid and 0-13 mol% of other diacid components; k. The diacid component of the polyester resin A is usually composed of 87-100 mol% of isophthalic acid and 0-13 mol% of other diacid components selected from the following: one or more aliphatic, alicyclic and / or aromatic diacids, such as terephthalic acid, fumaric acid, maleic acid, phthalic anhydride, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, succinic acid, adipic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,12-dodecanedicarboxylic acid, undecanedioic acid, tridecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, heptadecanedioic acid, octadecanedioic acid, or their corresponding anhydrides, and any mixtures thereof, most preferably 1,4-cyclohexanedicarboxylic acid (CHDA) and adipic acid; l. The sum of the polyol and polybasic organic carboxylic acid components of the polyester resin A having at least 3 OH groups usually accounts for 0-10 mol% of the total amount of polyols and carboxylic acids of the polyester resin A, preferably trimethylolpropane and trimellitic anhydride; m. The carboxylic acid-functional polyester resin component A is preferably prepared by reacting all of the polyols with all of the dicarboxylic acids and polycarboxylic acids and / or their anhydrides in one step.
7. The powder coating composition according to any one of claims 1 to 6, wherein the curing catalyst C is selected from ethyltriphenylphosphonium bromide, tributylamine, 2-methylimidazole or a mixture thereof.
8. The powder coating composition according to any one of claims 1 to 7, wherein the glycidyl-functional acrylic resin B has at least one of the following properties: a. an epoxy equivalent of at least 280, preferably at least 320, more preferably at least 360 g / eq, and at most 500, preferably at most 450, more preferably at most 400 g / eq; b. a number average molecular weight (Mn) of at least 1000, preferably at least 1200, as determined by gel permeation chromatography (GPC); c. The glass transition temperature is 35-60°C, measured by differential scanning calorimetry (DSC) with a heating gradient of 10°C / min according to ASTM D3418; d. Brookfield cone and plate viscosity of 10,000-75,000 mPa.s, preferably 15,000-55,000 mPa.s, measured at 150 ° C according to ASTM D4287-88; e. The functionality is higher than 2.5 and lower than 8.5, the functionality being defined as the average number of glycidyl groups per molecule, calculated by "measured Mn" / EEW.
9. The powder coating composition according to any one of claims 1 to 8, wherein the glycidyl-functional acrylic resin B has the following properties: a. an epoxy equivalent of at least 280, preferably at least 320, more preferably at least 360 g / eq and at most 500, preferably at most 450, more preferably at most 400 g / eq; b. a number average molecular weight (Mn) of at least 1000, preferably at least 1500 and at most 2500, preferably at most 2000, as determined by gel permeation chromatography (GPC); c. The glass transition temperature is 35-50°C, measured by differential scanning calorimetry (DSC) with a heating gradient of 10°C / min according to ASTM D3418; d. Brookfield cone and plate viscosity is 10,000-40,000 mPa.s, preferably 15,000-25,000 mPa.s, measured at 150°C according to ASTM D4287-88.
10. The powder coating composition according to any one of claims 1 to 9, wherein the content of polyester resin A, acrylic resin B, catalyst C and optional β-hydroxyalkylamide D is 60-100 wt%, based on the total weight of the powder coating composition.
11. A powder coating composition according to any one of claims 1 to 10, wherein the composition has a gel time measured at 200°C of less than 100 seconds, preferably 20 to 50 seconds.
12. A powder coating composition according to any one of claims 1 to 11, wherein the composition provides an edge coverage rating of at least 2.0 when tested using the low pressure wet sponge test method ASTM D5162; and / or wherein the composition provides a corner coverage of greater than 10%, preferably greater than 15%, even more preferably greater than 20% according to standard test method for corner coverage of powder coatings ASTM D2967-7.
13. A method of providing good edge coverage of a metal substrate comprising the steps of: contacting an uncoated metal substrate having a surface and an edge with a single layer of a powder coating composition according to any one of claims 1 to 12; curing the powder coating composition; Wherein the powder coating composition provides an edge coverage of at least 2.0 when tested using the low pressure wet sponge test method ASTM D5162.
14. The method according to claim 13, wherein the curing is carried out at a temperature of 160-210°C, preferably 180-200°C, for 10-30 minutes, preferably 10-15 minutes.
15. The method according to claim 13 or 14, wherein the thickness of the single layer after curing is 50-125 μm.
16. A method for preparing the powder coating composition according to any one of claims 1 to 12, comprising the following steps: Preparing acrylic resin B in a reactor; · mixing the acrylic resin B with the catalyst C before or while leaving the reactor to form a BC mixture; or Mixing acrylic resin B with catalyst C by extrusion to form a BC mixture; or Mixing acrylic resin B with catalyst C by dry blending to form a BC mixture; Dry blending the BC mixture, polyester resin A and optional β-hydroxyalkylamide D to form a blend; extruding the blend to form a homogenized mixture; - Cool and grind the homogenized mixture.
17. An article, preferably having a metal substrate partially or fully coated with the powder coating composition of any one of claims 1 to 12 or a powder coating composition prepared by the method of claim 16.
18. A metal substrate prepared by the method according to any one of claims 12 to 15.
19. Use of a powder coating composition as claimed in any one of claims 1 to 12 or a powder coating composition prepared by the method of claim 16 for providing good edge coverage of a metal substrate by application of a single layer, wherein the powder coating composition provides an edge coverage of at least 2.0 when tested by the low pressure wet sponge test method ASTM D5162.
Citation Information
Patent Citations
Hydroxyalkylamide powder coating curing system
EP0322834A2
Process for the preparation of hydroxyamides
EP0473380A1
Binder composition for powder coatings
EP0522648A1
Two-coat single cure powder coating
US10940505B2
Powder coating compositions based on mixtures of acid group-containing materials and beta-hydroxyalkylamides
US4727111A